Pengembangan Sistem Aplikasi Pemakaian Meteran Air dengan Pengolahan Gambar: Studi Kasus Layanan Air Desa Sindangsari - Ahmad, Umar Ali; Ramdani, Ikbal; Isham, Fath Muhammad; Dwiputra S, R Roger; Pratama, Yusup Diva; Alam, Rifdo Shah; Sofyan, Fauzi; Septiawan, Reza Rendian; Nugraheni, Ratna Astuti; Rusdinar, Angga; Dinimaharawati, Ashri; Abdurahman, M Ammar (JURNAL INFOTEL, 2024)
PAMDES is a drinking water company managed by local villagers. The water meter data are read and recorded manually without any technology, which is ineffective and inefficient. Digital image processing can be implemented to read and record the water meter data automatically. When implemented in the water meter, it can help PAMDES officers to read the data without the internet, without changing the conventional water meter device, and the water meter data can be read and recorded effectively and efficiently. This research used the agile method, one of the methods used in the Software Development Life Cycle (SDLC). The method is done repetitively within a short period of time. The output of this research is an application with a digital image processing model that can read water meter data up to 82% in normal conditions and still can be improved. This research aims to make the water meter data reading and recording more effective and efficient and to contribute to the transformation of Sindangsari village into a digitalized village.